A clinical, radiological and etiological study of neonatal pneumonia - Kobal, Mallikarjun R.; Gadgi, Prashant S.; Dhanwadkar, Sharanabasappa S.; N. B., Ashwini Kumari (International Journal of Contemporary Pediatrics, 2019)
Background: Pneumonia contributes to between 7, 50,000 and 1.2 million neonatal deaths and an unknown number of stillbirths each year worldwide1. It is estimated that 3.9 million of the 10.8 million deaths in children annually worldwide occur in the first 28 days of life.2 Neonatal pneumonia can be preventable if it is diagnosed as early as possible. Early recognition and prompt management are essential for the better outcome. Aim and objective: To determine bacterial etiology of neonatal pneumonia and to study the risk factors associated with neonatal pneumonia. Methods: A prospective, descriptive study was conducted for the duration of one year from July 2014 to June 2015 in Pragna children’s Hospital, a tertiary care centre, Hyderabad, Telangana, India. A total of 100 neonates were admitted in Pragna children’s Hospital with the signs and symptoms of neonatal pneumonia. A detailed history was taken including age, obstetric history of the mother, detailed birth history including resuscitation details and gestational age assessment were evaluated. Results: Out of 100 cases, 39(39%) neonates were preterm babies and 61(61%) were term. Also found history of Prolonged Rupture of Membrane (PROM) in 22% cases, maternal fever in 18%, home deliveries in 14% and foul smelling liquor in 18%. Out of 100 cases, 51 (51%) cases had positive finding in Chest X-Ray for neonatal pneumonia and 57(57%) had pneumonia with septicemia. Out of 100 cases, 9% of cases are positive for Coagulase negative staphylococcus (CONS), 5% for Klebsiella pneumonia, 2% for Pseudomonas aeroginosa and the remaining 84% of the cases had no growth for any organism. Conclusions: Major predisposing factors included PROM, foul smelling liquor, maternal fever, and home deliveries. CONS was the commonest organism isolated in blood culture.